2007
DOI: 10.1186/1471-244x-7-48
|View full text |Cite
|
Sign up to set email alerts
|

The assessment of depression awareness and help-seeking behaviour: experiences with the International Depression Literacy Survey

Abstract: Background: Depression causes substantial disease burden in both developed and developing countries. To reduce this burden, we need to promote understanding of depression as a major health condition. The International Depression Literacy Survey (IDLS) has been developed to assess understanding of depression in different cultural and health care settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 24 publications
1
22
0
Order By: Relevance
“…Information on demographics (age, gender and area of origin), personal and social experience with depression, and current psychological distress status (K10 which measures psychological symptoms on a 10-50 scale) were also collected at baseline as being previously embedded in the IDLS [22]. …”
Section: Methodsmentioning
confidence: 99%
“…Information on demographics (age, gender and area of origin), personal and social experience with depression, and current psychological distress status (K10 which measures psychological symptoms on a 10-50 scale) were also collected at baseline as being previously embedded in the IDLS [22]. …”
Section: Methodsmentioning
confidence: 99%
“…This may be related to a relatively low likelihood of seeking help, which has been found in previous studies of both student and general populations of Asians in the United States. 17,2224 Special efforts to reduce stigma and promote help-seeking in culturally sensitive ways may be appropriate for this population.…”
Section: Commentmentioning
confidence: 99%
“…Studies of depressed Hispanics and African-Americans have found that they often attribute depression to difficult life circumstances or stressors, deemphasizing medical etiology (Cabassa et al, 2008; Cabassa et al, 2007; Karasz, 2008; Alverson et al, 2007). International studies of depressed individuals have also found etiologic attributions to vary across cultural groups (Angermeyer et al, 2005; Hickie et al, 2007; Nakane et al, 2005; Shankar et al, 2006). These explanatory models may assign milder illness attributions to depression and influence help-seeking choices and reactions to proposed treatments (Guarnaccia et al, 1992; Guarnaccia et al, 2003; Lewis–Fernandez et al, 2005).…”
Section: Socio-cultural Factors Related To Sdmmentioning
confidence: 99%